A visão dos atores no sistema de drenagem urbana : uma análise crítica na gestão dos recursos humanos - Noccetti, Talita Fávaro (2008)
This research treats about the insights for: preparation of actors who are answerable for urban drainage systems in their performance on the public services. At first the work made a bibliography study about urban drainage system, riches being, formation and capacitance to act as an agent on the drainage system. To evaluate the High Education Engineering Institutions and Municipal Services were developed and applied questionnaires with specific approaches about the urban drainage system. After developed methodology to apply the questions for Municipal Services, were estimated the answers and it was insufficient. Then another search was made in official agencies, to obtain a detailed statistics report, and finally, with the data basis constructed, explain some conclusions and insights. The questionnaires were quite clear that Municipal Service is indifferent when the abstract is urban drainage, principally concerning the absence of answers. With the evaluate about the detailed report of the available municipal information, and the approach about future tendencies, the conclusion is have a hidden preoccupation in some towns with environment and is possible that this preoccupations can extend for drainage system. However some factors show negligence principally on direction of: better practices, regulation, inspection and paradigm changes, resulting in the same confront problems exiting on big cities, which have chronic environment and drainage problems. When the center of interest is the professional actors on drainage system and their education, considering the low improvement showed on questionnaires for the searched on High Education Institutions, was possible observed there are low tendencies about include, on engineering courses, the subjects embodying urban drainage system and another environment themes related. Notwithstanding, nowadays its possible may further mention this is insufficient.